MODERN VIEW OF MASS MEDIA - INFORMATION COMMUNICATION TECHNOLOGY - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages,; Qobulova Xonazim, Odiljonova Zarina, Abduraufova Gulmira, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
Various technologies have been developed over the years in terms of information and communication. Some of them had many versions as well. However, the feasibility of technology is to the extent it is cost effective to its users and it survives till it is taken over by an alternative far more superior and cost effective technology.